Childhood separation from parents with cognitive and psychopathological outcomes in adolescence. Issue 3 (15th September 2022) - Zhao, Xudong; Zhang, Anhui; Liu, Wanxu; Tao, Fangbiao; Sun, Ying
Abstract: To examine the effects of childhood parent‐child separation with varying duration and form on later cognitive performance and psychopathological problems over a 6‐year period, we use data from the China Family Panel Study (CFPS), which is an ongoing, prospective nationally representative study across 25 provinces in China. Of the 4033 children aged 4–10 years followed in 2012, 3522 children with complete data on separation from fathers and mothers were included. In 2018, 2560 participants were followed and interviewed to assess cognitive performance, behavioral problems as well as depressive symptoms at age 10–16 years. A total of 3522 children (mean [SD] age at baseline, 6.9 [2.0] years) were included. About 17.9% and 13.3% had separated from father and mother over 11 months or more in the year prior to the survey. Prolonged separation from parents was associated with lower scores in vocabulary (maternal: adjusted β = ‐1.64, P  = 0.002; paternal: adjusted β = ‐1.58, P  < 0.001) and mathematics performance (maternal: adjusted β = ‐1.10, P  = 0.009; paternal: adjusted β = ‐0.94, P  = 0.004) over a 6‐year period. Prolonged maternal separation was associated with 0.34‐point higher internalizing behaviors ( P  < 0.001) and 0.21‐point higher externalizing behaviors ( P  = 0.009), as well as 0.89‐point higher depressive symptoms ( P  = 0.018), while prolonged paternal separation was associated with 0.23‐point higher internalizing behaviors ( P  = 0.005) and 0.76‐point higher depressive symptoms ( P  = 0.011). The finding demonstrates substantial negative impacts of childhood paternal and maternal separations on cognitive and mental well‐being during adolescence, which might be dependent on the "stress‐dose" (duration of separation) and urban‐rural residence. Research Highlights: Prolonged parent‐child separation is independently associated with cognitive impairment and psychopathological problems during adolescence. The adverse effects of childhood separation on cognition and psychopathology varied by separation duration and separation forms. Age‐ and residence‐specific associations between parent‐child separation with cognition and psychopathology are observed. Abstract :